Dana Desa dan Demokrasi dalam Perspektif Desentralisasi Fiskal - Isto Widodo (Politik Indonesia: Indonesian Political Science Review)
Dana Desa (Village Fund) Program is targetting equal economic growth based on bottom up wealth growth. Constrastly, in its practice, there are some problems due its effect on program responsibility and on socio-political relation. Based on Theory of Fiscal Decentralization, this paper presenting the practice of Dana Desa Program in Desa Bajo, Soromandi, Bima, Province of NusaTenggara Barat (West Nusa Tenggara/NTB). We found that the effect of democracy capacity weakness that causing low government capacity as main source of the problems. Instead of gaining its aims, Dana Desa is trigging political and governmental problems in Desa Bajo. Low democracy capacity as the main source of the problemms, caused by internal and external factors i.e. political culture, institutional framework as well as factor of political actors and political institutions.